Jakarta Struts for Dummies - Robinson, Mike (Wiley Publishing, 2011)
As a Web developer, you’ve probably heard a lot about Jakarta Struts, the popular open source framework for creating Web applications in Java. Struts is the de facto standard for Java-based Web applications; in fact, some people consider it the yardstick by which all other Web application frameworks are measured.